Bóg jako pedagog w pismach prorockich odnoszących się do wspólnej historii Izraela i Edomu - Raszewski, Marek (Verbum Vitae, 2006)
In the article, concerning the prophetic interpretation of God’s pedagogy revealed in the history of Israel and Edom, we have presented a reconstruction of prophetic proclamations concerning both lsrael and the neighboring nations which were personified by Edom. Although the prophets focused their attention mainly on Israel and Judah, they knew that Yahweh was the Lord of all the nations and no nation remained outside His judgment. What He condemned and punished in His nation, he also condemned and punished in other nations. We have come to a conclusion, that in the analyzed prophetic texts there are also, apart from the foretelling of Edom’s punishment, prophetic appeals for Edom’s participation in the Messianie salvation. The Holy Bible analysis, especially the analysis of the prophetic book on Edom that we have presented, points to a gradual rise of the chosen nation’s awareness of the fact that God loves all men. This plays a significant role in God’ s pedagogy revealing different aspects of God’ s love, on one band foretelling Edom’ s punishment and on the other: its salvation.